Migraine and sleep. How is their relationship formed? - Bozhenko Наталія; Bozhenko Мирослав; Olga Боженко (Psychosomatic Medicine and General Practice, 2024)
Actuality: Many patients with migraines note that sleep significantly impacts the course of their disease. Clinicians and epidemiological studies have recognized the association between migraine and sleep disorders for centuries. Nevertheless, the exact nature of this connection and the underlying mechanisms remain not fully understood. Methods: 64 patients with migraine were examined, and the relationship between migraine attacks and sleep was evaluated. An analysis of the potential pathophysiological mechanisms that link migraine and sleep was carried out based on the analysis of publications, followed by the formulation of the main approaches regarding the possibilities of using this in daily clinical practice. Results and Discussion: Only 31.2% of migraine sufferers were delighted with their sleep quality. Among patients with chronic migraine, only 7.7% were delighted with their sleep quality. Migraine patients noted the following sleep disturbances: insufficient duration, dissatisfaction with sleep, difficulty falling asleep, nightmares, and daytime sleepiness. 32.8% of migraine sufferers noted sleep disturbance as one of the triggers that provoke migraine attacks. Recent biochemical and neuroimaging studies have identified central nervous system structures and neurotransmitters involved in the pathophysiology of migraine, as well as important for regulating standard sleep architecture, suggesting a possible causal role in the pathogenesis of both disorders of the dysregulation of these shared networks. Dysfunction of the hypothalamus and thalamocortical networks, as well as the glymphatic system, may be the main common areas involved in the pathological mechanisms of migraine and sleep disorders. Based on the analysis, 10 points were proposed that can help in everyday clinical practice. Conclusion: Sleep disorders and migraines are pathogenetically related and, therefore, are prevalent comorbid diseases. The current understanding of the neurobiological mechanisms underlying the comorbidity of migraine with sleep disorders still needs to be improved. However, it can be assumed that both pathogenes are based on the dysfunction of the hypothalamus and thalamocortical networks and the work of the glymphatic system. Routine assessment of the presence of complaints of sleep disturbances in patients with migraine and the use of specific pharmacological and non-pharmacological methods of treatment of sleep disturbances would be appropriate, as it may have a positive effect on reducing the burden of migraine.